Penyampaian Informasi Kesehatan Melalui Leaflet Tentang Kenali dan Cegah Stunting Pada Ibu Kondisi Hamil dan Ibu Mempunyai Balita - Azizah, Marshanda Wan; Rahmatillah, Mustafa; Sari, Okta Muthia (Universitas Respati Indonesia, 2025)
Stunting remains a significant health issue in Indonesia and poses a risk of hindering human resource development in the future. Efforts to prevent stunting must be initiated early through enhancing the knowledge of pregnant women and mothers of young children regarding the symptoms, causes, and preventive measures. Health information dissemination activities aim to improve participants' knowledge through leaflets about stunting. The method used was face-to-face health information dissemination, supplemented with leaflets as supporting materials, followed by an evaluation of participants' knowledge. The activity involved 10 pregnant women and mothers of young children in the service area of the Landasan Ulin Timur Health Center. Evaluation results showed an increase in knowledge, as indicated by the average score before and after the health information dissemination, which rose from 80% to 100%. This indicates that leaflets are effective as a health promotion tool to enhance public understanding of stunting. In conclusion, leaflets can serve as a simple, practical, and efficient educational alternative in efforts to prevent stunting in the community. Similar activities are recommended to be conducted continuously with the support of healthcare personnel, ensuring optimal prevention of stunting.